Toward a European definition for a drug shortage: a qualitative study - De Weerdt, Elfi; Simoens, Steven; Casteels, Minne; Huys, Isabelle (Frontiers in Pharmacology, 2015)
Background: Drug shortages are currently on the rise. In-depth investigation of the problem is necessary, however, a variety of definitions for ‘drug shortages’ are formulated in legislations, by different organisations, authorities and other initiatives. For international comparison, the underlying definition for drug shortages is important to allow appropriate interpretation of national databases and the results of scientific studies. The objective is to identify the different elements which should be considered in a uniform definition for drug shortages in the European Union and to detect the different conditions for reporting drug shortages. Methods: Definitions of drug shortages were searched in the scientific databases as well as in the grey literature. Similar topics were identified and organisations were contacted to formulate the reasoning underlying the definitions. Results: Over 20 different definitions for drug shortages were identified. A distinction is made between general definitions of drug shortages and definitions used for the reporting of drug shortages. Differences and similarities are observed in the elements within the definitions, e.g. when does a supply problem become a drug shortage, permanent and/or temporally shortages, the typology and time frame of a drug shortage. The moment a supply problem is considered as a shortage, can be defined at four levels: (i) demand side, (ii) supply side, (iii) delivery of a drug and (iv) availability of a drug. Permanent discontinuations of drugs are not always covered in definitions for drug shortages. Some definitions only consider those drugs used for the treatment of serious diseases or drugs for which no alternative is available. Different time frames were observed, varying between one day and 20 days. Conclusion: Obtaining a uniform definition for drug shortages is important as well as identifying which conditions are preferable to report drug shortages in order to facilitate international benchmarking. This paper can be used as a guidance to point out all the different elements which should be considered to formulate a uniform definition to be applied in the European Union.